2011
DOI: 10.1523/jneurosci.2301-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Fukutin-Related Protein Alters the Deposition of Laminin in the Eye and Brain

Abstract: Mutations in fukutin-related protein (FKRP) are responsible for a common group of muscular dystrophies ranging from adult onset limb girdle muscular dystrophies to severe congenital forms with associated structural brain involvement. The defining feature of this group of disorders is the hypoglycosylation of ␣-dystroglycan and its inability to effectively bind extracellular matrix ligands such as laminin ␣2. However, ␣-dystroglycan has the potential to interact with a number of laminin isoforms many of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…Recently, it was suggested that laminin deposition is altered within the cerebral cortex of FKRP knock-down mice (Ackroyd et al , 2011). The laminin staining pattern in FKRP knock-down mice is similar to that observed for POMGnT1 knockout mice (Hu et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was suggested that laminin deposition is altered within the cerebral cortex of FKRP knock-down mice (Ackroyd et al , 2011). The laminin staining pattern in FKRP knock-down mice is similar to that observed for POMGnT1 knockout mice (Hu et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inner limiting membrane (ILM), a BM of the retina is disrupted (Ackroyd et al, 2011;Hu et al, 2010;Lee et al, 2005;Satz et al, 2008). Additionally, DG (Williamson et al, 1997), POMT1 (Willer et al, 2004), and POMT2 (Hu et al, 2011a) null embryos die due to disruptions in Reichert’s membrane, an extra-embryonic BM.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the pathogenesis of the dystroglycanopathies further, we previously generated a mouse model of dystroglycanopathy which has a deficiency in fukutin-related protein (FKRP KD ). This mouse recapitulates some of the features of MEB; displaying a profound reduction in the glycosylation of alpha dystroglycan at the pial basement membrane, associated with basement membrane defects and a neuronal migration disorder [29,30]. In the dystroglycanopathies, this brain phenotype has been attributed to the inability of the radial glial end feet to maintain integrity of the pial basement membrane during the period of rapid cortical expansion; a process considered central to the neuronal migration defect in these disorders [31,32].…”
Section: Introductionmentioning
confidence: 82%
“…FKRP plays a role in glycosylation of α‐dystroglycan, an extracellular glycoprotein that mediates deposition of basement membranes by binding to various components such as laminin, perlecan, biglycan, agrin, and neurexin . Mutations in FKRP result in hypoglycosylation and downregulation of α‐dystroglycan and lead to disruption of basement membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the lens capsule, an uninterrupted basement membrane surrounding the ocular lens, became defective in this patient, resulting in capsular opacification and cataract formation. Interestingly, it was demonstrated in an animal model that a reduced FKRP influences the ability of tissue‐specific (eye and brain) forms of α‐dystroglycan to direct deposition of laminin isoforms to form different basement membranes . Notably, immunohistochemical analysis of muscle tissue from the patient demonstrated normal merosin (laminin‐2).…”
Section: Discussionmentioning
confidence: 99%